Bright spots as climate‐smart marine spatial planning tools for conservation and blue growth. (6th September 2021) - Queirós, Ana M.; Talbot, Elizabeth; Beaumont, Nicola J.; Somerfield, Paul J.; Kay, Susan; Pascoe, Christine; Dedman, Simon; Fernandes, Jose A.; Jueterbock, Alexander; Miller, Peter I.; Sailley, Sevrine F.; Sará, Gianluca; et al.
Abstract: Marine spatial planning that addresses ocean climate‐driven change ('climate‐smart MSP') is a global aspiration to support economic growth, food security and ecosystem sustainability. Ocean climate change ('CC') modelling may become a key decision‐support tool for MSP, but traditional modelling analysis and communication challenges prevent their broad uptake. We employed MSP‐specific ocean climate modelling analyses to inform a real‐life MSP process; addressing how nature conservation and fisheries could be adapted to CC. We found that the currently planned distribution of these activities may become unsustainable during the policy's implementation due to CC, leading to a shortfall in its sustainability and blue growth targets. Significant, climate‐driven ecosystem‐level shifts in ocean components underpinning designated sites and fishing activity were estimated, reflecting different magnitudes of shifts in benthic versus pelagic, and inshore versus offshore habitats. Supporting adaptation, we then identified: CC refugia (areas where the ecosystem remains within the boundaries of its present state); CC hotspots (where climate drives the ecosystem towards a new state, inconsistent with each sectors' present use distribution); and for the first time, identified bright spots (areas where oceanographic processes drive range expansion opportunities that may support sustainable growth in the medium term). We thus create the means to: identify where sector‐relevant ecosystem change is attributable to CC; incorporate resilient delivery of conservation and sustainable ecosystem management aims into MSP; and to harness opportunities for blue growth where they exist. Capturing CC bright spots alongside refugia within protected areas may present important opportunities to meet sustainability targets while helping support the fishing sector in a changing climate. By capitalizing on the natural distribution of climate resilience within ocean ecosystems, such climate‐adaptive spatial management strategies could be seen as nature‐based solutions to limit the impact of CC on ocean ecosystems and dependent blue economy sectors, paving the way for climate‐smart MSP. Abstract : Ocean climate change ('CC') modelling may become a key decision‐support tool for marine spatial planning ('MSP'), but traditional modelling analysis and communication challenges prevent their broad uptake. Here, ocean CC modelling is used as input to a statistical method testing whether a climate signal emerges in the ecosystem conditions, resources and natural capital underpinning each MSP sector of interest, within the time‐frame of implementation of a real‐life plan. Identifying the distribution of climate change hotspots, bright spots and climate refugia in the ecosystem underpinning each sector allows for climate‐adaptive spatial management strategies to be developed, supporting sustainability aims alongside blue growth.